Change in sleep duration and proposed dietary risk factors for obesity in Danish school children. Issue 6 (24th September 2014) - Hjorth, M. F.; Quist, J. S.; Andersen, R.; Michaelsen, K. F.; Tetens, I.; Astrup, A.; Chaput, J.‐P.; Sjödin, A.
Summary: Background: Recent cross‐sectional studies found higher consumption of energy‐dense foods among children with short sleep duration; however, longitudinal studies examining changes in sleep and diet over time are needed. Objective: This study aimed to investigate prospective associations between changes in objectively measured sleep duration and alterations in proposed dietary risk factors for obesity in 8–11‐year‐old Danish children. Methods: Four hundred forty‐one children recorded dietary intake during seven consecutive days, along with accelerometer measurements estimating sleep duration at baseline and after ∼200 days. Results: Baseline sleep duration did not predict changes in dietary intake or vice versa (all P  ≥ 0.69). However, 1‐h lower sleep duration was associated with higher intake of added sugar (1.59 E%; P  = 0.001) and sugar‐sweetened beverages (0.90 E%; P  = 0.002) after 200 days with no change in energy density of the diet ( P  = 0.78). Conclusion: Our results suggest that a negative change in sleep duration is associated with higher intakes of sugar containing foods/beverages.